Physical exercise during coronavirus disease (COVID-19): Recommendations to remaining active in periods of confinement - Letieri, Rubens VinÍcius (2020)
The period of social isolation during the COVID-19 pandemic has led people to adopt behaviors that were not previously part of their routines. The need to maintain an active lifestyle, with the adoption of an exercise regimen, has been reinforced by the scientific community for the maintenance of the immune and mental condition. Thus, we point out the need to observe the scientific guidelines on physical exercises during social isolation.